2022
DOI: 10.1001/jamaoncol.2022.1968
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Pegasparaginase-Based Chemotherapy Regimen vs an L-asparaginase–Based Chemotherapy Regimen for Newly Diagnosed Advanced Extranodal Natural Killer/T-Cell Lymphoma

Abstract: IMPORTANCEThe L-asparaginase-based SMILE (dexamethasone, methotrexate, ifosfamide, L-asparaginase, and etoposide) chemotherapy regimen has shown higher response rates and survival benefit over an anthracycline-containing regimen. However, the safety profile was not satisfied. A well-tolerated regimen with promising efficacy is lacking.OBJECTIVE To compare the efficacy and safety of the DDGP (dexamethasone, cisplatin, gemcitabine, and pegaspargase) regimen with the SMILE regimen in newly diagnosed advanced-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Asparaginase converts asparagine and glutamine to aspartate and glutamate, respectively, thereby decreasing plasma concentrations of asparagine and glutamine which ultimately reduces glutamine availability to the cancer cells 56 . Recent studies support the use of asparaginase and asparaginase derivatives as cancer therapeutics 9,10,52,57,58 . Mesothelioma is a highly aggressive and treatment‐resistant cancer, and our findings suggest that asparaginase‐dependent glutamine depletion may be a useful mesothelioma treatment strategy.…”
Section: Discussionmentioning
confidence: 69%
“…Asparaginase converts asparagine and glutamine to aspartate and glutamate, respectively, thereby decreasing plasma concentrations of asparagine and glutamine which ultimately reduces glutamine availability to the cancer cells 56 . Recent studies support the use of asparaginase and asparaginase derivatives as cancer therapeutics 9,10,52,57,58 . Mesothelioma is a highly aggressive and treatment‐resistant cancer, and our findings suggest that asparaginase‐dependent glutamine depletion may be a useful mesothelioma treatment strategy.…”
Section: Discussionmentioning
confidence: 69%
“…41.8%, P = 0.004) and 5-year OS (74.3% vs . 51.7%, P = 0.02) in the DDGP arm were significantly higher than those in the SMILE arm ( 130 ). L-Asp-based CT was inferior to PEG-Asp-based CT, at least in part due to the long L-Asp dosing interval between two courses of CT.…”
Section: The Role Of Asp In Enktcl Treatmentmentioning
confidence: 73%
“…In another recent randomized controlled study, 80 newly diagnosed ENKTCL patients were assigned to the DDGP (dexamethasone, cisplatin, gemcitabine, and PEG-Asp, repeated at 3-week intervals) arm or the SMILE (dexamethasone, methotrexate, ifosfamide, etoposide, and L-Asp, L-Asp given at 3-week intervals on days 3 to 9) arm. The results showed that the 3-year PFS (56.6% vs. 41.8%, P = 0.004) and 5-year OS (74.3% vs. 51.7%, P = 0.02) in the DDGP arm were significantly higher than those in the SMILE arm (130). L-Asp-based CT was inferior to PEG-Asp-based CT, at least in part due to the long L-Asp dosing interval between two courses of CT.…”
Section: L-asp and Pegaspargasementioning
confidence: 94%
See 1 more Smart Citation
“…In NKTCL, L-asparaginase-containing treatment regimens such as SMILE (dexamethasone, methotrexate, ifosfamide, L-asparaginase, etoposide) ( 81 , 82 ), P-GEMOX (pegaspargase, gemcitabine, and oxaliplatin) ( 83 ), DDGP (dexamethasone, cisplatin, gemcitabine, and pegaspargase) ( 84 ), and AspaMetDex (pegaspargase, methotrexate, and dexamethasone) ( 85 ) have been regarded as the preferred first-line therapy for advanced disease ( 67 ). Similar to PTCL, the role of hematopoietic stem cell transplant in NKTCL is highly controversial ( 29 , 86 ).…”
Section: Present-day Treatment Landscape Of Ptcl and Nktclmentioning
confidence: 99%